La represión de lo imaginario en el campo literario Mexicano del siglo XX - Vélez García, Juan Ramón (Acta Hispanica, 2010)
This work seeks to study, within the Mexican literary field of the XXth century, the situation of some authors who have been segregated from it because of their refusal to yield their work to the requirements of nationalistic themes. I’m going to take as examples of the aforementioned ideas two illustrative cases: the authors who were members of the group Contemporáneos (such as Xavier Villaurrutia, José Gorostiza, Jorge Cuesta, Gilberto Owen, Salvador Novo…) and the writer Francisco Tario (pseudonym adopted by Francisco Peláez).